2020
DOI: 10.3389/fpsyg.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Teachers’ Need for Cognition in Their Use of Technology in Mathematics Instruction

Abstract: Modern technology offers an increasing number of tools for teaching mathematics, but technology adoption in schools encounters many barriers. The Technology Acceptance Model explains that technology usage is dependent on intentions, which rest on perceived ease of use and perceived usefulness. Less is known about the relationship between intentions and actual behavior. In the current study we show that the level of cognitive investment on the part of the teachers, captured by the construct of Need for Cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
1
9
0
1
Order By: Relevance
“…Thus, in this study it could be shown, that this aspect is also reflected in the occupational context. Small positive associations between COM, SR and experience of social support (Study 1) could be found, which is in line with findings by Tanas et al (2020) and stresses COM and SR as resources also in terms of social variables.…”
Section: Active Meaningful and Persistent Copingsupporting
confidence: 90%
“…Thus, in this study it could be shown, that this aspect is also reflected in the occupational context. Small positive associations between COM, SR and experience of social support (Study 1) could be found, which is in line with findings by Tanas et al (2020) and stresses COM and SR as resources also in terms of social variables.…”
Section: Active Meaningful and Persistent Copingsupporting
confidence: 90%
“…Similarly, [27] affirmed that teachers are motivated if they receive support from the Educational Centre, considered as institutional determinants in the didactics of mathematics [2]. In contrast, a lack of support, especially from the management team, combined with low motivation on the part of the students, is associated with the burnout of teaching staff and abandonment of the teaching role [25]. Nevertheless, in line with the results for the indicators MTA and FCD used in this study, various authors have proposed that the use of ICT improves student learning and performance [23,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the support perceived by the teacher drives the incorporation of pedagogical ICT resources [25]. Furthermore, digital competence and motivation are correlated with their integration in the classroom [26].…”
Section: Attitudes Towards Ictmentioning
confidence: 99%
“…keinen signifikanten Zusammenhang zwischen der extrinsischen Zielorientierung und der tatsächlichen Nutzung digitaler Technologien im Unterricht fest. Bai et al (2019) und Tanas et al (2020) untersuchten jeweils den Zusammenhang von Interesse und Nutzungsintention bzw. Kognitionsbedürfnis und tatsächlicher Nutzung digitaler Technologien bei berufstätigen Lehrenden.…”
Section: Zielsetzung Und Fragestellung Der Vorliegenden Arbeitunclassified